Monitoring gleb zlokalizowanych wokół Huty Miedzi "Głogów" = Monitoring of the soils in the areas surrounding Copper Smelter "Głogów" - Przewocka, Marta; Rosada, Janusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Monitoring of soils is a form of the long-term ecological research. Increasingly, it becomes the main method to track the dynamics of physicochemical processes in the soil, as a result of agricultural and nonagricultural human activities. Since 1995 the chemistry monitoring of agricultural soil of Poland has been regarded as a subsystem of the National Environmental Monitoring of soil and land quality.
Keywords: zanieczyszczenia; gleba; monitoring; Huta Miedzi "Głogów"; soils; pollution; "Głogów" Copper Smelter